(untitled) (Analysis in Theory and Applications, 2014)
In this paper, we will prove the boundedness of Hardy type operators H_β(x) and H^*_β(x)of variable order β(x) on Herz spaces K^α(·)_p(·), qand K^α(·)_p(·), q, where α(·) and p(·) are both variable.